2003
DOI: 10.1111/j.1365-2311.2003.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of carbon and nitrogen from pollen and nectar by a predaceous larva and its effects on growth and development

Abstract: Abstract.  1. Predaceous insects may benefit from feeding on non‐prey foods, such as pollen, nectar, and honeydew, because they can provide nutrients that help maintain metabolism and enhance overall nutrient intake. Yet, the extent to which predaceous insects can assimilate non‐prey food and the importance of diet mixing during particular life history stages is poorly understood. In this study the relative contribution of an omnivorous diet to the growth and survivorship of a predaceous larva was tested in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 61 publications
3
57
0
6
Order By: Relevance
“…Moreover, the authors found a large proportion of unaltered starch in C. carnea feces. Alternatively, as pointed out by Patt et al (2003), apart from the nutritional value of macro-nutrients found in pollen, vitamins, mineral nutrients and sterols are important for digestion and other metabolic processes (Stanley & Linskens 1974, Waldbauer & Friedman 1991. Thus, differences in the digestibility and assimilation of nutrients from different pollen species are expected to have influence on predator fecundity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors found a large proportion of unaltered starch in C. carnea feces. Alternatively, as pointed out by Patt et al (2003), apart from the nutritional value of macro-nutrients found in pollen, vitamins, mineral nutrients and sterols are important for digestion and other metabolic processes (Stanley & Linskens 1974, Waldbauer & Friedman 1991. Thus, differences in the digestibility and assimilation of nutrients from different pollen species are expected to have influence on predator fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional value of such food varies with predator species and circumstances in which they find themselves. For some predaceous species non-prey items are essential during a non carnivorous life stage (Principi & Carnard 1984, Hickman & Wratten 1997, and for others plant-food may act as a supplement until nutritional optimal prey is located or as a complement of a suboptimal prey (Eubanks & Denno 1999, Evans et al 1999, Beckman & Hurd 2003, Patt et al 2003. Green lacewings are polyphagous predators whose larvae are carnivorous and adults have varied feeding habits with species being either carnivorous or glyciphagous and polliniphagous (Principi & Carnard 1984).…”
mentioning
confidence: 99%
“…63,64), siendo, especialmente en estos estadios larvario, excelentes aliados contra estos fitófa-gos (New, 1988b;McEwen et al, 2001;Miller et al, 2004), y a veces son muy selectivas, elemento que contribuye a la citada especificidad de sustrato sobre los que a veces hallamos los imagos de algunas especies. A veces son predadoras de huevos de otras especies de crisopas o de otros insectos (Canard, 1970bCarvalho et al, 1998), y complementan su dieta con levaduras, polen y néctar (Hagen & Tassan, 1970;Patt et al, 2003), y en más de una ocasión (y no es broma) el autor ha observado alguna "osada larva antropófaga" introduciéndome sus mandíbulas por algún pliegue de mi piel con la "maliciosa" intención de obtener de mí algún fluido como alimento.…”
Section: (Ver Suarius Walsinghami)unclassified
“…Little information is available regarding isotopic and trophic changes associated with metamorphosis, from feeding during the larval and adult stages through starvation during the chrysalis stage. Also, pollen and nectar are basal resources in terrestrial food webs (e.g., Memmott 1999;O'Reilly et al 2002, Patt et al 2003, and feeding on pollen and nectar by pollinators is important for maintaining plantpollinator interactions and terrestrial food webs (Memmott 1999). However, investigations of feeding on pollen and nectar would be difficult using only bulk d 15 N values (Patt et al 2003), because large variations exist among the d 15 N values of these foods.…”
Section: Introductionmentioning
confidence: 99%